Improving Environmental Literacy on the Dangers of Microplastics and Reducing Single-Use Plastics through an Environmentally Friendly School Program at Al-Razi Sinar Harapan Vocational High School Medan - Ahmad Hafizullah Ritonga; Herlina Herlina; Karnirius Harefa; Rotua Sumihar Sitorus; Ihsanul Hafiz (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Microplastics and the extensive use of single-use plastics have become growing environmental issues that threaten human health and ecosystem sustainability. Limited environmental literacy among adolescents contributes to the continued high consumption of single-use plastics in school settings, highlighting the need for effective environmental education programs. This community service activity aimed to improve students’ environmental literacy regarding the dangers of microplastics and the importance of reducing single-use plastic use through an environmentally friendly school program at Al-Razi Sinar Harapan Vocational High School, Medan. The program involved 58 students and was implemented through interactive educational sessions, group discussions, simple demonstrations on plastic pollution, and campaigns promoting the use of reusable tumblers and food containers. Evaluation was conducted through participatory observation and assessment of students’ responses during discussions and question-and-answer sessions. The results indicated that participants were able to explain the concept of microplastics, identify common sources of plastic pollution within the school environment, and propose practical alternatives to reduce single-use plastic consumption, including the use of reusable containers, tumblers, and cloth bags. Increased participation during discussions, improved ability to answer questions related to the educational materials, and students’ expressed commitment to adopting environmentally friendly practices served as indicators of enhanced understanding and environmental awareness following the program. The activity also received positive feedback from teachers and school administrators and contributed to fostering a cleaner, healthier, and more sustainable school environment.